O ensino de PBE no mundo dos negócios : gêneros textuais e escrita - Duarte, Andrea Lima Belfort (2009)
The growth of globalization in the latter half of the 20th century has brought with it many profound transformations in our society. In business, a growing internationalization of the production and commercialization of goods and services is clearly visible, catalyzed by technological advances and greater flexibility between borders of nations, especially in socio-economic and financial terms. However, national borders within business have not been quite as flexible. Understanding both the language and the culture of a foreign business can contribute to success in a entrepreneurial context. Given this context, some books have been published in recent years to teach Portuguese to foreigners interested in establishing business with Brazil. In this study, materials published in Brazil with a focus in teaching Portuguese for the purpose previously described were analyzed. Our analysis identified the discoursive genres offered for study. It's result was contrasted with data obtained from questionaries related to the discoursive genres that were produced in portuguese by foreigners enrolled in the world of business in Rio de Janeiro, seeking to verify their suitability in the context of international business. The research showed that there is, in general, a low rate of production tasks based on written genres and they do not meet the writing requirements for the target audience. This demonstrates the need to invest in improving and developing materials that address the issue of the writing text focused on different genres within business in a more comprehensive way.